On the potential intermediacy of PhIBr 2 as a brominating agent - Tania; Molino, Andrew; Sharp-Bucknall, Lachlan; Wilson, David J. D.; Dutton, Jason L. (Organic & biomolecular chemistry, 2022)
PhIBr 2 , first purported to exist over 100 years ago, has been subject of few reports due to its low stability. However, a recent publication proposes a reaction of PIFA (PhI(OC(O)-CF 3 ) 2 ) with TMSBr to form PhIBr 2 in situ and demonstrated its efficacy in aryl brominations. This report investigates this synthesis by replicating bromination reactions claiming to use in situ PhIBr 2 as described. The spectroscopical and computational results indicate formation of PhI and Br 2 where Br 2 is responsible for bromination and no supporting evidence for invoking PhIBr 2 as an intermediate is found.